SINGLE STEP SYNTHESIS OF H-MWCNTS AND ITS APPLICATION AS VISIBLE LIGHT DRIVEN PHOTOCATALYST IN DYE DEGRADATION STUDIES - A.SARAVANAN; A. ABILARASU; T. SOMANATHAN (International Journal of Pharma and Bio Sciences, 2015)
In this work, we have synthesized carbon nanotubes CNTs in a single step and tested for photocatalytic activity under visible light. The synthesized CNTs were characterized using XRD, SEM, HRTEM and Raman spectroscopy. The surface characterization of the CNTs reveals that the morphology seems to be helical multi walled carbon nanotubes (h-MWCNTs). The dependency of photodegradation to variables such as contact time, pH, catalyst weight, H2O2 concentration and dye concentration were investigated and optimized. The results implies that the CNTs play a vital role in degradation studies at pH 3 with very trace amount of CNTs as a photocatalyst. This suggests that the ability of CNTs will able to store and shuttle the electrons available in the visible region for dye degradation which can possibly used in environmental remediation.